CONSUMER PREFERENCES IN MAKING DECISIONS TO PURCHASE TRADITIONAL SNACKS AT TENANK CAFE, MEDAN CITY - Nasfia Arsila Nisa; Agustinawati; Lisa Iryani; Sufi; Nursakinah Ritonga (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study discusses consumer preferences in making purchasing decisions for traditional snacks at Tenank Cafe, Medan City. This study aims to analyze consumer preferences for purchasing decisions for traditional snacks at Tenank Cafe, Medan City. The independent variables in this study are price, tangible, and food quality. While the dependent variable in this study is the purchasing decision. This type of research is quantitative. The population used in this study were all consumers at Tenank Cafe, Medan City. The sample used was 100 respondents with a non-probability sampling method with an accidental sampling technique. Data collection was carried out using a questionnaire distributed to Tenank Cafe consumers. Data processing and data analysis techniques were carried out using the SPSS 26 program. The results of this study indicate that price (X1) has a positive and significant effect on purchasing decisions (Y) for traditional snacks at Tenank Cafe with a t-count value of 7.303> 1.985 and a sig value of 0.000 <0.05. Tangible (X2) has a positive and significant effect on purchasing decisions (Y) of traditional snacks at Tenank Cafe with a calculated t value of 5.520> 1.985 and a sig value of 0.000 <0.05. The results of the food quality variable (X3) have a positive and significant effect on purchasing decisions (Y) of traditional snacks at Tenank Cafe with a calculated t value of 8.352> 1.985 and a sig value of 0.000 <0.05. If done together, price, tangible, and food quality have a positive and significant effect on purchasing decisions (Y) of traditional snacks at Tenank Cafe with a calculated f test result of 32.790> 3.94 and a sig value of 0.000 <0.05.